(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2010)
Leishmaniasis is an important health and social problem for which there is limited effective therapy. Chalcones and N-acylhydrazones have been studied as promising antileishmanial agents in enzymatic inhibition and in vitro assays. Since these chemical classes of compounds also resemble each other structurally, it would be useful to investigate whether they share direct analogy. Exploratory data analysis was applied to a library of chalcones and nitrated N-acylhydrazones assayed against Leishmania donovani to investigate their similarity. Under the conditions applied in the present study, the two classes did not present functional or structural analogy.